2008
DOI: 10.2474/trol.3.366
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Dynamic Properties of O-rings and Stability Threshold of Flexibly Supported Herringbone Grooved Aerodynamic Journal Bearings

Abstract: The purpose of this paper is to measure the non-linear dynamic properties of O-rings in wide frequency ranges including in the ultra-high-speed rotational regions and to calculate the stability threshold of herringbone grooved aerodynamic journal bearings with O-rings support. First, the Voigt model was used as a rheological model of the O-rings, and the spring and the damping coefficients were evaluated in a wide frequency range from 0.5 to 4 kHz. Then, the stability threshold of the herringbone grooved aerod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
4
11
0
Order By: Relevance
“…One main reason for the difficulty would be that the dynamic stiffness and damping of the O-rings depend on the operating conditions such as excitation frequency and temperature of the bearing system, as well as the design factors such as the materials and the deformation ratios of the O-rings. The authors [18] already confirmed from the comparison of the analysis and the experiment that it was possible to predict the whirl onset speed accurately by considering the frequency dependence of the support stiffness and damping of the O-rings. Then, the empirical formulae with a clear physical meaning were proposed to be able to treat the dynamic properties of the O-rings in various bearing support conditions [19,20].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…One main reason for the difficulty would be that the dynamic stiffness and damping of the O-rings depend on the operating conditions such as excitation frequency and temperature of the bearing system, as well as the design factors such as the materials and the deformation ratios of the O-rings. The authors [18] already confirmed from the comparison of the analysis and the experiment that it was possible to predict the whirl onset speed accurately by considering the frequency dependence of the support stiffness and damping of the O-rings. Then, the empirical formulae with a clear physical meaning were proposed to be able to treat the dynamic properties of the O-rings in various bearing support conditions [19,20].…”
Section: Introductionmentioning
confidence: 85%
“…In the past publication, Tomioka and Miyanaga [18] expressed the both coefficients by cubic equations in the frequency range less than 4.0 kHz. However, the cubic equations cannot accurately fit the stiffness and damping coefficients in the wide frequency range, from 0.5 to 8.0 kHz.…”
Section: Identification Of Stiffness and Damping Coefficientsmentioning
confidence: 99%
“…These tendencies agree with previous reports 4), in which the constants (Table 3) were determined by fitting to the experimental results here. (Belforte et al 2008;Tomioka and Miyanaga 2008;Smalley 1977;Darlow and Zorzi 1981;Smalley, Darlow, and Mehta 1978;Al-bender et al 2017). When the damping coefficient was plotted instead of as in literature (Tomioka and Miyanaga 2008), decreased with .…”
Section: Dynamic Properties Of O-ring Componentsmentioning
confidence: 99%
“…Because high-speed turbo machinery experiences vibration frequencies exceeding 100 Hz, the BERM (base excitation resonant mass) method was utilized in this study. BERM is applicable for frequencies of more than 100 Hz and is often used for determining the dynamic properties of O-rings (Tomioka and Miyanaga 2008;Darlow and Zorzi 1981).…”
Section: Dynamic Properties Of O-ring Componentsmentioning
confidence: 99%
See 1 more Smart Citation